On the hydration and conformation of cocaine in solution - Gillams, R; Lorenz, C; McLain, S (Elsevier, 2017)
In order to develop theories relating to the mechanism through which cocaine can diffuse across the blood-brain barrier, it is important to understand the interplay between the hydration of the molecule and the adopted conformation. Here key differences in the hydration of cocaine hydrochloride (CHC) and freebase cocaine (CFB) are highlighted on the atomic scale in solution, through the use of molecular dynamics simulations. By adopting different conformations, CHC and CFB experience differing hydration environments. The interplay between these two factors may account for the vast difference in solubility of these two molecules.